Immunotoxins in cancer therapy: Review and update. (4th July 2017) - Akbari, Bahman; Farajnia, Safar; Ahdi Khosroshahi, Shiva; Safari, Fatemeh; Yousefi, Mohammadreza; Dariushnejad, Hassan; Rahbarnia, Leila
ABSTRACT: Immunotoxins are a novel class of cancer therapeutics that contains a cytotoxic agent fused to a targeting moiety. Various toxic agents from different sources are used in immunotoxin development, including bacterial, plant and human origin cytotoxic elements. Although bacterial and plant-derived toxins are highly toxic and commonly used in immunotoxins, their immunogenicity for human restricted their application in cancer therapy. Here, we discuss the advantages and limitations of bacterial toxins such as Pseudomonas and Diphtheria toxins, plant toxins such as ricin and gelonin, and some endogenous protein of human origin such as RNases and Granzymes. This article will also review different generations of immunotoxins with special focus on immunotoxins which are under clinical trials or approved for clinical use. Finally, current deimmunization strategies for development of new less-immunogenic recombinant immunotoxins will be discussed. Abbreviations: mAbs: Monoclonal antibodies; EF2: elongation factor 2; ITs: Immunotoxins; DT: Diphtheria toxin; PE: Pseudomonas exotoxin; dgA: de-glycosylated A-chain of ricin; rGel: recombinant de-glycosylated form of gelonin; NKC: natural killer cells; HTR: human transferrin receptor; EGF: epidermal growth factor; GM-CSF: granulocyte-macrophage colony-stimulating factor; DAB389: truncated Diphtheria toxin; B-CCL: B-cell chronic lymphocytic leukemia; RCC: renal cell carcinoma; GVHD: Graft-versus-host disease; EGFR: epidermal growth factor receptor; AML: acute myeloid leukemia; Fab: fragment antigen-binding; dsFv: disulfide-stabilized fragment variable; scFv: single-chain fragment variable; B-ALL: B-lineage Acute Lymphoblastic Leukemia; Fv: fragment variable; HCL: hairy cell leukemia; IL-2R: Interleukin-2 receptor; CR: complete response; CLL: chronic lymphocytic leukemia; ATL: adult T-cell leukemia; DARPins: designed Ankyrin repeat proteins; pmol: picomolar; HAMA: human-anti mouse antibody